From gaspaža to kundze: female honorifics in Latvian in the 16th–19th centuries - Vanags, Pēteris (Vilnius University Open Series, 2022)
This article focuses on those modern and historical Latvian words that, in addition to the main component of the meaning ‘adult woman’, also include the components of respect and/or social status, namely, gaspaža, madama, dāma, and kundze. The article discusses the emergence and change of use of these lexemes in the 16th–19th century with a special focus on the processes of the middle and second half of the 19th century. In less than a century, the semantic field of the honorific female designations in the Latvian language has undergone significant changes. From one word gaspaža to four in the 1870s, but the most significant changes took place in the last twenty years of the century. In formal and neutral use, kundze and dāma were strengthened, each occupying a different part of the semantic field, competing synonymously only in the general sense of ‘honorable woman’, as well as in the function of address. However, even in this case, kundze is more often used in the context of the singular and dāma in the plural. In turn, lexemes gaspaža and madama have become characteristic of colloquial language and fiction; they often have an ironic or negative connotation.